Bacterial taxonomic representation of Hypothyroid Breast Milk and Infant Faecal samples with OTU Heat Maps and Rare Faction Curves - Lebonah, D. Esther; PramodaKumari, J. (International Journal of Scientific Research in Biological Sciences, 2020)
The alterations of gut bacterial communities provoke disease conditions in humans. Gut bacterial dysbiosis is one of the causes of hypothyroidism. Maternal gut bacteria migrate towards the mammary glands via an endogenous cellular route and later inhabit the gastrointestinal tract of the breast-fed neonate through the entero-mammary pathway. So, it is necessary to expose the abundance and richness of bacteria inhabiting both in breast milk and infant’s gut. The study showed that the high number of OTUs (Operational Taxonomic Units) related to the many classes of bacteria and rarefaction curves related to some fraction of unidentified species diversity in all the samples.